2022
DOI: 10.21608/svu.2022.119853.1176
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Mushroom Extracts against Butyl Paraben Induced Toxicity in Liver and Kidney in Female Albino Rats.

Abstract: Parabens are group of preservatives chemical compounds used in cosmetics, personal hygiene product, food products and pharmaceuticals. In this study the hepatorenal toxicity due to exposure to paraben was evaluated. In this study design Twenty-four of albino rats experimentally used. Butyle paraben (BP) orally was given to animals 180 days in dose of 4.6 mg\kg.bw which equal to10 % of the LD50 of BP. The extract of Mushroom was given by stomach tube in dose of 10 mg/kg/day for six 180 days. Exposure to Paraben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…The alterations in gills, like epithelial lifting, hyperplasia, and fusion of epithelial cells, were also reported by Camargo and Martinez [ 47 ]. A similar alteration in histology of the gills after exposure to paraben, as recorded by Beriry, Atef [ 43 ] supports our present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The alterations in gills, like epithelial lifting, hyperplasia, and fusion of epithelial cells, were also reported by Camargo and Martinez [ 47 ]. A similar alteration in histology of the gills after exposure to paraben, as recorded by Beriry, Atef [ 43 ] supports our present study.…”
Section: Discussionsupporting
confidence: 93%
“…The results of serum biochemical showed that all these parameters were elevated significantly as compared to the control group. These results were supported by the findings of Beriry, Atef [ 43 ] and Darbre and Harvey [ 44 ]. The increases in liver enzymes occur directly in response to liver toxicity caused by ethylparaben in hepatocytes.…”
Section: Discussionsupporting
confidence: 84%
“…Changes in kidney structure can influence urea levels. 16 In our research, various findings were observed in the examined kidney tissues, including glomerular atrophy, tubular degeneration, and structural deterioration. Therefore, it is speculated that the decreased serum urea value is a result of kidney impairment.…”
Section: Discussionmentioning
confidence: 61%
“…14 Studies on parabens and endocrine-disrupting chemicals have reported increased serum ALT and AST levels. 3,[15][16][17] The most common reason for elevated serum ALT levels is likely plasma membrane injury, with ALT activity increasing significantly during hepatocyte damage and necrosis. 17 In our research, necrotic areas were observed in the dose groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation